On a stochastic interacting particle system with pushing dynamics - Abdukadyrov, Nurlan (Nazarbayev University School of Science and Technology, 2016)
In this paper we study a stochastic two-particle system on Z where particles interact each other by pushing dynamics. We derive the explicit formulas of the transition probability and of the probability distributions of each particle's position at time t. Finally, we discuss about the generalization of our works to N-particle system.
Keywords: Research Subject Categories; stochastic interacting particle system